M2M gateway selection scheme for smart wireless devices - Vidanagama, Tharinda Nishantha; Arai, Daisuke; Ogishi, Tomohiko (2015 18th International Conference on Intelligence in Next Generation Networks, 2015)
Wireless standardization activities such as the Bluetooth V4.x (Bluetooth smart) have led to an explosive growth in innovative short-range wireless devices capable of providing various services to assist everyday life. Allowing Machine-to-Machine (M2M) communication between these M2M devices also enable new commercial service opportunities. The M2M service providers including telecom carriers may need to establish new networks to accommodate M2M interactions while identifying new business opportunities. Typically M2M devices need another capable device such as a smartphone to act as a gateway to connect to the Internet to operate at its full potential. We propose a scheme where any Internet enabled device in the surrounding environment can act as an M2M gateway for M2M devices. This eliminates the need for the M2M device user to also own an Internet enabled device such as a smartphone to obtain services such as Online-to-Offline. This scheme faces new challenges such as, how to identify a best M2M gateway for a required service and QoS etc. This paper proposes a method to select an M2M gateway among many others, in order to increase service availability while obtaining better signal strength for higher QoS. The performance of the proposed method is evaluated using real world data collected at an exhibition with encouraging results.